A combined study of the thermoluminescence and electron paramagnetic resonance of point defects in ZrO2:Er3+. (July 2020) - Lokesha, H.S.; Chithambo, M.L.
Abstract: This work describes thermoluminescence of beta irradiated zirconium oxide (ZrO2 ) doped with erbium. The sample was synthesized by the solution combustion method. Kinetic analysis of the thermoluminescence is reported and paramagnetic defects sensed by electron paramagnetic resonance (EPR) have been investigated. Using X-ray diffraction, the phase of the sample was determined to be monoclinic. Glow curves measured at 1 °C s −1 show two peaks at 50 °C (peak 1) and at 112 °C (peak 2). The dose response of peak 1 is sublinear within 51–411 Gy whereas that of peak 2 is linear between 51 and 155 Gy becoming sublinear thereafter up to 411 Gy. Peak 1 fades within 1800 s of irradiation whereas peak 2 fades to 59% of its initial intensity within 14, 600 s of irradiation. Kinetic analysis of the peaks was done using the initial rise, whole glow peak and curve fitting methods. The order of kinetics of both peaks was determined to be first order. The activation energy of peaks 1 and 2 were found to be 0.67 ± 0.01 eV and 0.71 ± 0.02 eV respectively. The EPR spectrum of erbium doped ZrO2 reveals that there are two types of Zr 3+ ions present in the sample as distinguished by their coordination in the material. The F + type centres are generated during sample irradiation and these centres accountable for the TL peaks. Highlights: ZrO2 :Er studied was synthesized by solution combustion techniques. TL and dosimetric features of beta irradiated ZrO2 have been investigated. Kinetic analysis of two prominent peaks (50 °C and 112 °C ) is reported. Attempts have been made to use EPR data to interpret TL features.